Remember Your Name, Babylon - Van Cauwenberghe, Bram (Belgium, 2015)
The film follows the lives of a group of men and women, brought together in Europe by fate, who crossed the sea from North Africa and the Middle East in search of a better life. They live in a no man’s land, somewhere on the coast of Spain between long rows of hermetically sealed greenhouses, waiting for news of their immigration status.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Brumagne, Marie; Documentary films